Structural Characteristics of the Guaiacyl-Rich Lignins From Rice (Oryza sativa L.) Husks and Straw - Rosado, Mario J.; Rencoret, Jorge; Marques, Gisela; Gutiérrez, Ana; del Río, José C. (Frontiers in Plant Science, 2021)
Rice (Oryza sativa L.) is a major cereal crop used for human nutrition worldwide. Harvesting and processing of rice generates huge amounts of lignocellulosic by-products such as rice husks and straw, which present important lignin contents that can be used to produce chemicals and materials. In this work, the structural characteristics of the lignins from rice husks and straw have been studied in detail. For this, whole cell walls of rice husks and straw and their isolated lignin preparations were thoroughly analyzed by an array of analytical techniques, including pyrolysis coupled to gas chromatography-mass spectrometry (Py-GC/MS), nuclear magnetic resonance (NMR), and derivatization followed by reductive cleavage (DFRC). The analyses revealed that both lignins, particularly the lignin from rice husks, were highly enriched in guaiacyl (G) units, and depleted in p-hydroxyphenyl (H) and syringyl (S) units, with H:G:S compositions of 7:81:12 (for rice husks) and 5:71:24 (for rice straw). These compositions were reflected in the relative abundances of the different interunit linkages. Hence, the lignin from rice husks were depleted in β–O–4′ alkyl-aryl ether units (representing 65% of all inter-unit linkages), but presented important amounts of β–5′ (phenylcoumarans, 23%) and other condensed units. On the other hand, the lignin from rice straw presented higher levels of β–O–4′ alkyl-aryl ethers (78%) but lower levels of phenylcoumarans (β–5′, 12%) and other condensed linkages, consistent with a lignin with a slightly higher S/G ratio. In addition, both lignins were partially acylated at the γ-OH of the side-chain (ca. 10-12% acylation degree) with p-coumarates, which overwhelmingly occurred over S-units. Finally, important amounts of the flavone tricin were also found incorporated into these lignins, being particularly abundant in the lignin of rice straw.